Livro ilustrado e primeira infância: leituras que excedem palavras - Mariana Parreira Lara do Amaral (2021)
Picturebooks, increasingly recurrent in the Brazilian publishing industry, are complex works whose concept is still in the process of formulation. By highlighting the picturebook in literary production for children this research analyses works awarded by ‘Fundação Nacional do Livro Infantil e Juvenil’ – FNLIJ, from 1975 to 2020. It has been intended to scrutinise the possible transformations occurred in the role of illustration, its association with the verbal text as well as with the object, in order to define the constitution of the Brazilian picturebook. In light of the historical course of children’s literature in the West, the particularities of the picturebook are examined considering it as an artistic object. The contributions of Michel Melot (2015), Odilon Moraes (2019), Sophie Van der Linden (2011), Martin Salisbury and Morag Styles (2012), Rui de Oliveira (2008b) and Maria Nikolajeva and Carole Scott (2011) supported the analysis and conclusions of the work. The methodology consisted of examining the award-winning books within the categories “Child”, “Picture Book”, “Best Illustration” and “Toybook”. Analysing the data enabled the organisation of the collection into seven main categories: 1st) Text and images: spaces in dispute; 2nd) The silence of the word and the narrative image; 3rd)The design of the word; 4th) Materiality and narrative; 5th) Metafiction and intertextuality; 6th) Brazil expressed in visuality and 7th) Authorship: references and paradigms. Aspects of convergence between the works were observed, within the four dimensions of space-time: line, page, book and time (ALENCAR and COELHO, 2016). The path of this research reinforces the complexity and potentiality of picturebook and indicates that this way of narrating is predominant in the most recent FNLIJ awards, within the categories scrutinised. The trajectory of the awards also demonstrates that even before the use of the term “picturebook” in Brazil, it is possible to observe a process of the image’s ascension, allied to the exploration of the book as an object. The pedagogical resource that integrates this research, in ebook format, addresses the issues of training readers, of literary mediation and of the narrative elements that constitute picturebooks, establishing a dialogue between research and teaching action, especially those developed within the scope of early childhood education.